Vinylogous functionalization of 4-alkylidene-5-aminopyrazoles with methyl trifluoropyruvates - Hostalet-Romero, Judit; Carceller-Ferrer, Laura; Blay, Gonzalo; Sanz-Marco, Amparo; Pedro, José R.; Vila, Carlos (Beilstein Journal of Organic Chemistry, 2025)
A valuable vinylogous addition reaction between 4-alkylidene-5-aminopyrazoles and alkyl trifluoropyruvates leading to highly functionalized tertiary alcohols bearing a trifluoromethyl group and a pyrazole ring is presented. The corresponding trifluoromethyl alcohols are obtained in moderate to good yields (up to 80%) and high diastereoselectivity (up to 7:1).
Keywords: alcohols; diastereoselectivity; nitrogen heterocycles; pyrazoles; vinylogous reaction